Gestión administrativa del distrito de educación 12d01 y su efecto en el nivel de satisfacción de los usuarios del Cantón Babahoyo Año 2015. - Vera Márquez, César Darwin (2016)
The present research was developed in the Education District 12D01 Babahoyo, an institution dedicated to providing services to the educational community. Administrative management in the public sector is always present in institutions, to provide service with quality, efficiency and effectiveness; The lack of an administrative control results in the internal disinformation of the organization. The objective of the present investigation was to establish the administrative management that optimizes the level of satisfaction of the users of the education district 12D01. In the analysis of the administrative management was made through a consensus with the employees and departmental heads to determine the strengths, weaknesses, opportunities and threats of the institution, evidence the weaknesses that exist and for. Reducing the incidence of these weaknesses proposes strategies to convert weaknesses in strengths and threats into opportunities, tending to the continuous improvement of the same, optimizing the services through the training of human talent.